2013
DOI: 10.1128/iai.00043-13
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Infection-Associated Periodontal Bone Resorption Is Dependent on Receptor Activator of NF-κB Ligand

Abstract: dPorphyromonas gingivalis is one of the oral microorganisms associated with human chronic periodontitis. The purpose of this study is to determine the role of the receptor activator of nuclear factor-B ligand (RANKL) in P. gingivalis infection-associated periodontal bone resorption. Inbred female Rowett rats were infected orally on four consecutive days (days 0 to 3) with 1 ؋ 10 9 P. gingivalis bacteria (strain ATCC 33277). Separate groups of rats also received an injection of anti-RANKL antibody, osteoprotege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 35 publications
(52 reference statements)
6
53
0
1
Order By: Relevance
“…In the current study, in line with previously reported data [68] P. gingivalis DNA was detected in the oral cavity of the periodontitis-affected animals, although the presence of P. gingivalis in metacarpophalangeal joint tissue of periodontitis-affected animals could not be detected. To our knowledge, P. gingivali s DNA in synovial tissue in experimental animal models has not yet been reported.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, in line with previously reported data [68] P. gingivalis DNA was detected in the oral cavity of the periodontitis-affected animals, although the presence of P. gingivalis in metacarpophalangeal joint tissue of periodontitis-affected animals could not be detected. To our knowledge, P. gingivali s DNA in synovial tissue in experimental animal models has not yet been reported.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous rat models of periodontal disease showed similar results, i.e., the levels of RANKL mRNA and protein expression positively correlated with the level of bone resorption, and RANKL blockage by anti-RANKL antibody led to significantly decreased bone loss (40,41). In this study, the decreased RANKL/ OPG ratio in mouse gingival tissue injected with anti-RANKL antibody further substantiated the effect of RANKL blockage in the bone resorption process (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…RANKL blockade has been successful in animal models of periodontitis (180)(181)(182). Patients treated with anti-TNF-α therapy for other disorders have also shown some improvement in alveolar bone loss (183).…”
Section: Therapeutic Perspectivementioning
confidence: 99%